Metaheurísticas GRASP e ILS aplicadas ao problema da variabilidade no tempo de download em ambientes de TV digital - Ramos, Daniel Gonçalves (2012)
The arrival of Digital TV has brought the possibility to broadcasters create interactive programs. For this, applications should be sent to the TV station via the standard DSMCC carousel. This standard enables data to be sent cyclically, so that any time you turn on the TV, it can receive all data transmitted. However, the way each interactive application will be available on the carousel has an impact on the users waiting time. The carousel can be modified to prioritize some applications, and so give more satisfaction to most users and also increase the profits of the station. It is not been defined yet a model of how to handle the priority of applications. Current work suggests an innovative business model, seeking to satisfy users, the broadcaster and the contractor.With the priorities of the applications, a new problem arises, termed here as the Download Time Variability Problem (DTVP). It defines the way that the carousel should be created to minimize the users waiting times. This is a difficult problem, which makes the use of exact techniques unapplicable for large instances. The paper proposes the use of GRASP and ILS metaheuristics to solve the problem.